Pengaruh Budaya Organisasi, Kompensasi melalui Komunikasi Terhadap Kinerja Pegawai CV. Amandira Teknik - Muhammad Alhudori; Muhammad Oceano Fauzan (Universitas Batanghari, 2023)
In this study the variables used were organizational culture, compensation, communication, and performance of employees at CV. Amandara Engineering. The purpose of this research is to provide input to CV. Amandra Teknik and adds knowledge to readers. The research method used by distributing questionnaires to CV employees. Amandra Teknik, in answering the questionnaire the respondent simply marked the column that contained the Likert's Scale (1 – 5) above it. The results obtained from this study, partially organizational culture (X1) on communication (Y) has an insignificant negative effect, while compensation (X2) has a positive and significant effect on communication (Y), as well as organizational culture variable (X1) on performance (Z) has no significant negative effect, while compensation (X2) has a positive and significant effect on performance (Z) and the communication variable (Y) on performance (Z) partially has a positive and significant effect. Meanwhile, simultaneously organizational culture (X1), compensation (X2) through communication (Y) on performance (Z) has a positive influence. More about this source textSource text required for additional translation information.